2018
DOI: 10.1155/2018/9390784
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Green Synthesized Silver Nanoparticles Using Extract of Nepeta deflersiana against Human Cervical Cancer Cells (HeLA)

Abstract: In this study, silver nanoparticles (AgNPs) were synthesized using aqueous extract of Nepeta deflersiana plant. The prepared AgNPs (ND-AgNPs) were examined by ultraviolet-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscope (SEM), and energy dispersive spectroscopy (EDX). The results obtained from various characterizations revealed that average size of synthesized AgNPs was 33 nm and in face-centered-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
86
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(126 citation statements)
references
References 58 publications
18
86
3
Order By: Relevance
“…5). Contrary to our findings, the biosynthesized AgNPs from some medicinal plants such as Melia azedarach [70], Moringa olifera [71], Nepeta deflersiana [35] in the previous studies showed high cytotoxic effect on HeLa cells.…”
Section: Xrd Analysiscontrasting
confidence: 99%
See 3 more Smart Citations
“…5). Contrary to our findings, the biosynthesized AgNPs from some medicinal plants such as Melia azedarach [70], Moringa olifera [71], Nepeta deflersiana [35] in the previous studies showed high cytotoxic effect on HeLa cells.…”
Section: Xrd Analysiscontrasting
confidence: 99%
“…3. In this study, S. officinalis extract showed several spectra that indicate the complex nature of the plant extract and our findings corroborates with the results of Al-Sheddi et al [35]. The spectra of S. officinalis extracts displayed broad and strong absorbance peak at 3248 cm -1 that corresponds to O-H vibration, which could be arising from phenolic compounds or carboxylic group in the extract [58].…”
Section: Ftir Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…However, Olea-AgNPs significantly increased the late stage of apoptotic cells and necrotic cells in comparison to Lav-AgNPs-treated cells. The present results are in well accordance with previous studies that have reported cell death due to apoptosis as a result of nanoparticle exposure [43] and green synthesized silver nanoparticles from plant extract [44]. They concluded that DNA damage and in turn apoptosis/necrosis 7 Journal of Nanomaterials are linked to excessive production of reactive oxygen species, oxidative stress [45], and SubG1 arrest of cells due to nanoparticle treatment for cancer cells [44].…”
supporting
confidence: 93%